2023
DOI: 10.3390/horticulturae9020160
|View full text |Cite
|
Sign up to set email alerts
|

GA3 and Hand Thinning Improves Physical, Chemical Characteristics, Yield and Decrease Bunch Compactness of Sultanina Grapevines (Vitis vinifera L.)

Abstract: Nowadays, the Sultanina grapevines H4 strain has become widely cultivated because of its high productivity. However, this Sultanina variety is suffering from clusters with small berries, in addition highly compacted berries, thus negatively affecting the quality of bunch berries. A field experiment was carried out during the two successive seasons on Five years old Sultanina (H4 strain) grapevines grafted onto freedom rootstock grown in a private orchard located in El-Khatatba region, Minufyia Governorate, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Their study was on, how GA3 and Hand thinning improves the physical and chemical characteristics, yield and bunch compactness of sultanina grapevine. Result showed that the application GA3 at 30 ppm is effective for reducing the cluster compactness and improves physical and chemical parameters [9].…”
Section: Effect Of Gibberellic Acid On Physical Chemical Properties A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Their study was on, how GA3 and Hand thinning improves the physical and chemical characteristics, yield and bunch compactness of sultanina grapevine. Result showed that the application GA3 at 30 ppm is effective for reducing the cluster compactness and improves physical and chemical parameters [9].…”
Section: Effect Of Gibberellic Acid On Physical Chemical Properties A...mentioning
confidence: 99%
“…PGRs are also known as bio-stimulates and bio-inhibitors exist inside the plant cell to either stimulate or inhibit particular enzymes or enzyme systems and to control the metabolism of plant [8] Gibberellic acid is most often used as a reagent in chemical thinning. Berry thinning enhances berry weight and soluble solids, while decreasing bunch weight and loosening the bunch [9]. Spraying at bloom and fruit set stage promoting growth, and positively effects on lengthening cluster, berry size in a bunch thinning of seedless grapes [10].…”
Section: Introductionmentioning
confidence: 99%